Efikasi Bakasang sebagai imunostimulan pada pakan sidat (Anguilla marmorata) terhadap infeksi Aeromonas hydrophila - Janis, Olvi A.P.; Tumbol, Reiny A.; Longdong, Sammy (e-Journal BUDIDAYA PERAIRAN, 2016)
The purpose of this study was to examine the effect of fish silages, bakasang as an immunostimulant in eel (Anguilla marmorata) feed against Aeromonas hydrophila infection. Three hundred elvers with the size of + 10 cm taken from Freshwater Aquaculture Institute (BBAT) Tatelu. The elvers were placed into 4 glass aquarium, each equipped with aerator and 1 for stock. Prior to the study, the eels were acclimatized for two weeks in order to adapt to new environmental condition. Two sets of researches were done: feeding the eels with additional bakasang with different doses for 6 weeks, which then further were challenged with Aeromonas hydrophila by immersion method. This study used a completely randomized design (CRD) with 4 treatments A (0 mL /kg diet), B (50 mL/kg diet), C (100 mL/kg diet), D (150 mL/kg diet). The growth data was taken by measuring the weight and length of the eels at the end of the period of feeding treatment while the mortality data of the eels were observed for 10 days after challenge test.  The results of analysis of variance showed that the resistance of the eels in treatment B (50 mL/kg diet), C (100 mL/kg diet) and D (150 mL/kg diet) significantly different compared with treatment A.  However, among the treatments B, C and D, there were no significant differences.  Furthermore, the best eel growth was observed in treatment B with an absolute growth of 1.14 g, followed by treatment of D with an absolute growth of 1.04 g. In treatment A the absolute growth was only 0.82 g while treatment C was 0. 88 g.  This suggests that the addition of bakasang in eels feed can promote the growth of eels as well as resistance against pathogen infection, thus served as immunostimulant. Keywords: fish silages, immunostimulant, eel,  Aeromonas hydrophila, growth